First report of bacterial wilt caused by Ralstonia solanacearum on fig trees in China. Issue 3 (21st March 2016) - Jiang, Y.; Li, B.; Liu, P.; Liao, F.; Weng, Q.; Chen, Q.
Summary: This article presents the first report of bacterial wilt on fig ( Ficus carica ) trees in China. In 2014, fig trees with typical bacterial wilt symptoms were observed for the first time in China. The causal pathogen was determined to be Ralstonia solanacearum . Identification was based on symptomatology, morphology, BioLog carbohydrate utilization, 16S rDNA sequence analyses and phylotype‐specific multiplex‐PCR assays.